Experimental investigation of microexplosion occurrence in water in diesel emulsion droplets during the leidenfrost effect - Khan, M.Y. (American Chemical Society, 2014)
Microexplosion phenomenon is attributed for achieving simultaneous reduction of particulate matter and nitrogen oxides in diesel engine exhaust when water in diesel emulsion is used as fuel. In this work, an emulsion droplet suspended on a wire-type thermocouple on a hot plate as the heat source was used to study the evolution of microexplosion phenomenon of emulsions prepared by two different methods. Microexplosion behavior of emulsions produced by a homogenizer and mechanical stirrer with 5, 10, and 20 water by volume was visualized. A high-speed camera synchronized with a data-logging system was used to capture the events. The results show that the waiting time, puffing frequency, initial temperature drop, and microexplosion temperature were affected by the size and distribution of the dispersed water droplets. No microexplosion was observed for all of the homogenized emulsions, while all of the mechanically stirred emulsions developed microexplosions. Â© 2014 American Chemical Society.